Question
upstudy study bank question image url

Make the variable given after each equation the subject of the formula: a) \( \quad V=\pi r^{2} h \) for \( h \) b) \( \quad V=\pi r^{2} h \) for \( r \) c) \( \quad A=P(1+i n) \) for \( i \) d) \( \quad A=P(1+i)^{n} \) for \( i \) e) \( 3=\frac{-b+\sqrt{b^{2}-4 a c}}{2 a} \) for c f) \( s=u t+\frac{1}{2} a t^{2} \) for a g) \( s=u t+\frac{1}{2} a t^{2} \) for u h) \( \quad S A=2(l b+l h+b h) \) for h i) \( \quad 0=a x^{2}+b x+c \quad \) for \( a \) j) \( \quad T_{n}=a(r)^{n-1} \) for \( r \)

Ask by Harper Little. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) \( h = \frac{V}{\pi r^2} \) b) \( r = \sqrt{\frac{V}{\pi h}} \) c) \( i = \frac{A - P}{nP} \) d) \( i = \left(\frac{A}{P}\right)^{\frac{1}{n}} - 1 \) e) \( c = -9a - 3b \) f) \( a = \frac{2(s - ut)}{t^2} \) g) \( u = \frac{s - \frac{1}{2}at^2}{t} \) h) \( h = \frac{SA}{2} - lb \) divided by \( (l + b) \) i) \( a = -\frac{b x + c}{x^2} \) j) \( r = \left(\frac{T_n}{a}\right)^{\frac{1}{n-1}} \)

Solution

Below are one acceptable set of solutions. Note that there may be several equivalent ways to rearrange each equation. ───────────────────────────── a) Solve V = πr²h for h Step 1. Divide by πr²:   h = V⁄(πr²) ───────────────────────────── b) Solve V = πr²h for r Step 1. Divide by πh:   r² = V⁄(πh) Step 2. Take the square root (assuming r ≥ 0):   r = √[V⁄(πh)] ───────────────────────────── c) Solve A = P(1 + in) for i Step 1. Divide by P: 1 + in = A⁄P Step 2. Subtract 1: in = (A⁄P) – 1 Step 3. Divide by n: i = [(A⁄P) – 1]⁄n (Alternatively, one can write i = (A – P)/(nP).) ───────────────────────────── d) Solve A = P(1+i)ⁿ for i Step 1. Divide by P: (1+i)ⁿ = A⁄P Step 2. Take the nth root: 1+i = (A⁄P)^(1/n) Step 3. Subtract 1: i = (A⁄P)^(1/n) – 1 ───────────────────────────── e) Solve 3 = (–b + √(b² – 4ac))/(2a) for c Step 1. Multiply both sides by 2a (assuming a ≠ 0):   6a = –b + √(b² – 4ac) Step 2. Add b:   6a + b = √(b² – 4ac) Step 3. Square both sides:   (6a + b)² = b² – 4ac Step 4. Expand and simplify. Expand the left side:   36a² + 12ab + b² = b² – 4ac Step 5. Cancel b² from both sides:   36a² + 12ab = –4ac Step 6. Solve for c by dividing by –4a (assuming a ≠ 0):   c = –(36a² + 12ab)/(4a) = –9a – 3b ───────────────────────────── f) Solve s = ut + (½)at² for a Step 1. Subtract ut:   s – ut = (½)at² Step 2. Multiply by 2:   2(s – ut) = at² Step 3. Divide by t² (t ≠ 0):   a = 2(s – ut)/t² ───────────────────────────── g) Solve s = ut + (½)at² for u Step 1. Subtract (½)at²:   s – (½)at² = ut Step 2. Divide by t (t ≠ 0):   u = [s – (½)at²]/t ───────────────────────────── h) Solve SA = 2(lb + lh + bh) for h Step 1. Divide both sides by 2:   SA⁄2 = lb + lh + bh Step 2. Factor h from the terms that contain it:   SA⁄2 = lb + h(l + b) Step 3. Subtract lb:   SA⁄2 – lb = h(l + b) Step 4. Divide by (l + b) (assuming l+b ≠ 0):   h = [SA⁄2 – lb]⁄(l + b) ───────────────────────────── i) Solve 0 = ax² + bx + c for a Step 1. Write the equation as:   ax² + bx + c = 0 Step 2. Isolate ax²:   ax² = –bx – c Step 3. Divide by x² (assuming x ≠ 0):   a = –(bx + c)/x² ───────────────────────────── j) Solve Tₙ = a·r^(n–1) for r Step 1. Divide by a (a ≠ 0):   r^(n–1) = Tₙ⁄a Step 2. Take the (n–1)th root (provided n–1 ≠ 0):   r = (Tₙ⁄a)^(1/(n–1)) ───────────────────────────── These are the rearranged formulas with the indicated variable as the subject. Any algebraically equivalent form is correct.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To make the variable the subject of the formulas, we need to isolate it step-by-step. a) For \( V=\pi r^{2} h \) and solving for \( h \): \[ h = \frac{V}{\pi r^{2}} \] b) For \( V=\pi r^{2} h \) and solving for \( r \): \[ r = \sqrt{\frac{V}{\pi h}} \] c) For \( A=P(1+i n) \) and solving for \( i \): \[ i = \frac{A}{Pn} - 1 \] d) For \( A=P(1+i)^{n} \) and solving for \( i \): \[ i = ( \frac{A}{P} )^{\frac{1}{n}} - 1 \] e) For \( 3=\frac{-b+\sqrt{b^{2}-4 a c}}{2 a} \) and solving for \( c \): \[ c = \frac{b^{2}-4 a (3 \cdot 2 a)}{4 a} \] f) For \( s=u t+\frac{1}{2} a t^{2} \) and solving for \( a \): \[ a = \frac{2(s - ut)}{t^{2}} \] g) For \( s=u t+\frac{1}{2} a t^{2} \) and solving for \( u \): \[ u = \frac{s - \frac{1}{2} a t^{2}}{t} \] h) For \( S A=2(l b+l h+b h) \) and solving for \( h \): \[ h = \frac{SA/2 - lb}{b} - l \] i) For \( 0=a x^{2}+b x+c \) and solving for \( a \): \[ a = \frac{-b x - c}{x^{2}} \] j) For \( T_{n}=a(r)^{n-1} \) and solving for \( r \): \[ r = ( \frac{T_{n}}{a} )^{\frac{1}{n-1}} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy